Pavel Aleksadrovic Florenskij's method of discerning spiritual truth - C. Camilleri (Acta Theologica)
This article explores Pavel Florenskij’s dialectical method as the preferred way to discern spiritual truth. It presents the Russian polymath’s method within his socio-political and ecclesiastical contexts and two of his works, namely his magnum opus entitled The pillar and ground of truth, and his lecture Reason and dialectics, both of which are significant for interpreting Florenskij’s thought. The article also provides an intertextual reading of Florenskij’s Pillar to argue that its context is 1 Timothy 3:14-16. It then analyses the similarities between the context of 1 Timothy and that of The Pillar. As they fall within a period during which particular churches faced certain challenges, both texts call for discernment of the true identity of the church.